Literature Review Pengaruh Terapi Bekam Terhadap Penurunan Tekanan Darah pada Pasien Hipertensi - Cita Rahayuningsih; Dini Nurbaeti Zen; Yoga Ginanjar (Universitas Galuh, 2025)
Hypertension is one of the leading causes of morbidity and mortality worldwide, with its prevalence rising each year. Non-pharmacological therapies, such as cupping therapy, have become increasingly popular as alternative treatments for hypertension. This study aims to analyze the effects of cupping therapy on blood pressure reduction in hypertensive patients through a literature review. The method applied was a literature review using the PICOS approach. Articles were retrieved from Google Scholar, ScienceDirect, and PubMed using the keywords “Cupping Therapy”, “Wet Cupping”, “Blood Pressure”, and “Hypertension” from 2020 to 2025. A total of 10 articles met the inclusion and exclusion criteria and were critically appraised. The results showed that both dry and wet cupping therapy effectively reduced systolic blood pressure by 20.90 mmHg and diastolic pressure by 22.38 mmHg. The therapy was administered for 20–30 minutes, with a frequency of once a week to once a month for a duration of 2–3 months. Conclusion: Cupping therapy is effective as a complementary intervention in reducing blood pressure among hypertensive patients when applied regularly with proper duration and frequency.